The Risk of Oropharyngeal Cancer from E-Cigarette Use: An Urgent Public Health Concern - Cameron Y. S. Lee; Jon B. Suzuki (Journal of Public Health International, 2022)
It is estimated that over 47 million people use tobacco products, mostly in the form of combustible (smokable) tobacco cigarettes. Thirteen to 50% of smokers also use electronic cigarettes (also known as e-cigarettes or vaping). Use of tobacco is the primary preventable cause of death and risk factor for lung, head, neck, and oropharyngeal cancer. Electronic cigarettes are a 10 billion dollar industry and has the potential to surpass the tobacco cigarette market. E-cigarette use is a public health concern because of the health issues of vaping and the limited amount of scientific research to support the safety of e-cigarette use. The authors of this paper want to create awareness that use of e-cigarettes is not a safer alternative to smoking tobacco cigarettes as e-cigarettes contain known carcinogens that may lead to development of oropharyngeal cancer.
Keywords: tobacco cigarette